Between Symbols and Service: Inclusive Leadership in Faith-Based Hospitals, Identity Safety, and Interfaith Patient Trust in Yogyakarta - Qurratul Aini; Rini Eka Sari (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Faith-based hospitals in Yogyakarta operate within a pluralistic society where patient trust is shaped by both clinical competence and identity-sensitive service cues. Specific Background: Inclusive leadership is theorised to reduce identity threat and enhance fairness perceptions, yet empirical evidence on its effects for interfaith patients remains limited. Knowledge Gap: Existing studies have not clarified how leadership-driven identity-safe cues and justice perceptions jointly influence trust, affective comfort, and patient behavioural outcomes in faith-based healthcare. Aims: This study examines a structural model linking inclusive leadership, identity-safe religious cues, procedural/interactional justice, trust, comfort, satisfaction, and post-service behaviour. Methods: A cross-sectional survey of 114 outpatients from two urban hospitals was analysed using PLS-SEM. Results: Inclusive leadership strongly predicted identity-safe cues and fairness perceptions, which in turn significantly increased trust; trust enhanced comfort, driving satisfaction, revisit intention, and positive word of mouth. Novelty: This study reframes inclusive leadership as a consumer-facing signal of warmth, competence, and interfaith respect, advancing identity-safety theory into healthcare consumption. Implications: Hospitals should institutionalise inclusive cue architecture and transparent procedures to strengthen trust, elevate patient experience, and reinforce competitive advantage. Highlights: Inclusive leadership strengthens identity-safe religious cues and fairness signals. Trust and affective comfort act as key mediators toward satisfaction and loyalty. Identity-safe service design enhances interfaith patient experience and hospital competitiveness. Keywords: Inclusive Leadership, Identity-Safe Cues, Trust, Patient Comfort, Faith-Based Hospitals